Low mechano‐energetic efficiency is associated with future left ventricular systolic dysfunction in hypertensives - Maria V. Manzi; Costantino Mancusi; Maria Lembo; Giovanni Esposito; Maria A.E. Rao; Giovanni deSimone; Carmine Morisco; Valentina Trimarco; Raffaele Izzo; Bruno Trimarco (ESC Heart Failure, 2022)
Abstract Aims In a hypertensive population with optimal blood pressure control with a long‐term follow‐up, we aimed at analysing possible predictors of left ventricular (LV) ejection fraction (LVEF) reduction, including indexed mechano‐energetic efficiency (MEEi), a well‐recognized echo‐derived parameter of LV performance. Methods and results The study population included 5673 hypertensive patients from the Campania Salute Network with a long‐term follow‐up, normal baseline LVEF (≥50%), and no prevalent cardiovascular (CV) disease. Patients developing LVEF impairment (LVEF < 50% or a reduction of at least 10 percentage points compared with baseline) were compared with patients with persistently normal LVEF. Optimal blood pressure control was achieved in about 80% of patients. Patients who experienced LVEF reduction were 2.41% during a long‐term follow‐up (mean duration 5.6 ± 3.9 years). At baseline, they were older (59.46 ± 11.58 vs. 53.40 ± 11.41, P < 0.0001) and showed higher LV mass index (53.3 ± 12.83 vs. 47.56 ± 9.58, P < 0.0001), left atrial (LA) volume index (14.4 ± 4.2 vs. 13.1 ± 2.8, P < 0.0001) and carotid intima–media thickness (1.99 ± 0.86 vs. 1.61 ± 0.73, P < 0.0001), lower MEEi (0.32 ± 0.08 vs. 0.34 ± 0.07, P = 0.037), and higher prevalence of CV events during follow‐up (13.9% vs. 3%, P < 0.0001) compared with patients with persistently normal LVEF. A logistic regression analysis, performed after running univariate analyses and selecting parameters significantly associated with LVEF reduction, showed that having a CV event [odds ratio (OR) 7.57, P < 0.0001], being in the lowest MEEi quartile (OR 2.43, P = 0.003), and having a larger LA volume index (OR 1.08, P = 0.028) were all parameters independently associated with the development of LV systolic dysfunction. A further logistic regression model, performed by excluding patients experiencing CV events, demonstrated that the lowest MEEi quartile was independently associated with the evolution towards LVEF reduction (OR 2.35, P = 0.004), despite significant impact of LA volume index (OR 1.08, P = 0.023) and antiplatelet therapy (OR 1.89, P < 0.01). Receiver operating characteristic curves showed that the model including MEEi had higher accuracy than the model without MEEi in predicting LVEF reduction (areas under the curve 0.68 vs. 0.63, P = 0.046). Conclusions Lower values of MEEi at baseline identify hypertensive patients more liable to develop LVEF reduction. In hypertensive setting, MEEi evaluation improves risk stratification for development of LV systolic dysfunction during long‐term follow‐up.